2016
DOI: 10.1007/s13205-016-0524-5
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of endocrine disruptor dibutyl phthalate (DBP) by a newly isolated Methylobacillus sp. V29b and the DBP degradation pathway

Abstract: Bacteria of the genus Methylobacillus are methanotrophs, a metabolic feature that is widespread in the phylum Proteobacteria. The study demonstrates the isolation and characterization of a newly isolated Methylobacillus sp. V29b. which grows on methanol, protocatechuate, monobutyl phthalate, dibutyl phthalate, diethyl phthalate, benzyl butyl phthalate, dioctyl phthalate and diisodecyl phthalate. Methylobacillus sp. V29b was characterized with scanning electron microscopy, transmission electron microscopy, Gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 98 publications
1
19
0
1
Order By: Relevance
“…(Hu et al 2015). Kumar and Maitra (2016) also found MBP, PA and pyrocatechol as intermediate compounds during DBP degradation by Methylobacillus sp. Metabolites of degradation of DBP (initial concentration 1000 mg/l) by Rhizobium sp.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…(Hu et al 2015). Kumar and Maitra (2016) also found MBP, PA and pyrocatechol as intermediate compounds during DBP degradation by Methylobacillus sp. Metabolites of degradation of DBP (initial concentration 1000 mg/l) by Rhizobium sp.…”
Section: Discussionmentioning
confidence: 90%
“…Tang et al (2016) found that Rhizobium sp. LMB-1 had a removal capacity of nearly 100 mg of DBP/l within 60 h. Kumar and Maitra (2016) found that Methylobacillus sp. degraded 70% of DBP (initial concentration 2000 mg/l) after 192 h. Lee et al (2007) reported that the white rot fungus Polyporus brumalis nearly eliminated a concentration of 350 mg of DBP/l within 12 days and that the mycelial growth of the fungus was inhibited.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have focused on bioremediation as a low-cost tool for the restoration of contaminated soil, due to its effectiveness and overall promise compared to alternative physical and chemical techniques (Shahsavari et al 2013;Zhu et al 2016). Commonly, bioremediation refers to the use of microorganisms to transform or degrade a contaminant into harmless product(s) (Antizar-Ladislao 2010; Owabor et al 2010;Kumar and Maitra 2016). Biodegradation of PAHs has attracted widespread attention, and various bacteria with the ability to degrade individual PAHs have been isolated and identified (Chen et al 2015;Zafra et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The cost and efficiency are the first considerations in the implementation of remediation technologies. Bioremediation involves the utilization of microorganisms to breakdown or mineralize pollutants into less harmful or non-toxic compounds (Kumar and Maitra 2016). Its efficiency and cost-effectiveness make it a promising technology for the removal of pollutants.…”
Section: Introductionmentioning
confidence: 99%